Оценка нарушенных зон угленосной толщи - Карамушка, О.А. (Геотехническая механика, 2012)
Наведено результати аналізу порушених зон, виділених у вугільних пластах Павлоградсько-Петропавлівського і Донецько-Макіївського геолого-промислових районів Донбасу, на основі визначення кількості тектонічних блоків порід, їх розмірів і розрахунку їх коефіцієнтів форми. The results of analysis of the dislocated zone, selected in coal layers of Pavlogradsko-
Petropavlovskiy and Donetzko-Makeevskiy geological-industrial districts of Donbas on the basis of determining the percentage of tectonic blocks of rocks, their sizes and calculation of their coefficients of form are presented in the article.